2020
DOI: 10.1111/jfbc.13536
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identifying of α‐amylase inhibitors from medicine food homology plants: Insights from computational analysis and experimental studies

Abstract: There is a growing interest in screening α-amylase inhibitors from natural products for application in the development of new antidiabetic drugs or functional foods. In this study, a structure-based virtual screening was applied to rapidly identify the α-amylase inhibitors from medicine food homology (MFH) plants. Similarity search, docking & scoring were used for further filter small molecules. As a result, 21 corresponding potential α-amylase inhibitors from MFH plants were obtained. And, six polyphenol comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The inhibitory ability of different extracts and compounds 1–7 against α‐Amylase was determined, as mentioned previously with several simple modifications (Jiang et al, 2020). 80 μl of α‐amylase (1 mg/mL) mixed with different extracts and compounds 1–7 (0.1, 0.2, 0.4, 0.8, and 1.6 mg/mL) or acarbose (0.1, 0.2, 0.4, 0.8, and 1.6 mg/mL, positive control) were incubated in a water bath at 37°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibitory ability of different extracts and compounds 1–7 against α‐Amylase was determined, as mentioned previously with several simple modifications (Jiang et al, 2020). 80 μl of α‐amylase (1 mg/mL) mixed with different extracts and compounds 1–7 (0.1, 0.2, 0.4, 0.8, and 1.6 mg/mL) or acarbose (0.1, 0.2, 0.4, 0.8, and 1.6 mg/mL, positive control) were incubated in a water bath at 37°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Chen and colleagues assessed whether puerarin regulated the phosphorylation of Akt and AS160, as well as the protein level of total and membrane GLUT4 in soleus muscles of HFD/STZ-induced diabetic rats and 0.75 mM palmitate-incubated L6 cells. The results indicated that the contents of total and membrane GLUT4, as well as the rates of p-AS160/AS160 and p-Akt/Akt, in the puerarin treatment group were obviously higher than those in the model group, both in vivo and in vitro [ 26 ]. Taken together, this evidence suggested that puerarin could promote GLUT4-mediated glucose uptake by elevating GLUT4 mRNA and protein expression and upregulating the phosphorylation of Akt and AS160.…”
Section: Effect Of Puerarin On Glucose and Lipid Metabolismmentioning
confidence: 99%
“…Puerarin-treated HFD/STZ-induced diabetic rats showed significant upregulation of IRS-1 protein content and an increase in the ratios of pInsR(Tyr 1150/1151 )/InsR and pIRS-1(Tyr 612 )/IRS-1. Similarly, the levels of mRNA and of IRS-1 protein in palmitate-induced IR L6 cells treated by puerarin were obviously higher than that of model cells [ 26 ]. These results suggested that the regulation effect of puerarin on the PI3K–Akt signaling pathway and its downstream proteins may be achieved by improving insulin sensitivity.…”
Section: Effect Of Puerarin On Glucose and Lipid Metabolismmentioning
confidence: 99%
“…Significant changes in dietary intake during the past decades have been associated with the increase in the incidence of UC. Dietary factors can be related to UC pathogenesis or disease course through direct effects on the host or indirect effects through modulations of composition or function of gut microbiota, which plays a key role in UC treatment. For example, a meta-analysis study shows that the consumption of fruits and vegetables is related to a decreased chance of UC development. Therefore, the integration of a drug delivery system and edible food plants such as vegetables and fruits highlights its potential value of this unique hybrid material as a new food-grade drug delivery system. A food-grade drug delivery system can be defined as the entrapment of a bioactive ingredient in a food grade carrier to protect and improve drug release profiles . There are unique advantages of food grade oral drug-delivery systems, as they could: (1) mask the unpleasant taste or smell of some drugs, (2) protect bioactive molecules from undesirable conditions of the digestive tract such as enzymatic degradation, and (3) serve as a carrier and controlling the location and rate of release of the active constituent during the process of food digestion.…”
Section: Introductionmentioning
confidence: 99%